PENGEMBANGAN MEDIA PROMOSI KESEHATAN VIDEO ANIMASI MENGENAI GIZI SEIMBANG PADA REMAJA PUTRI TAHUN 2021 (Politeknik Kesehatan Kemenkes Bandung, 2021)
The case of nutrition in Indonesia is still a concern of the government in balanced nutrition interventions. One of the nutritional problems that is still high is obesity in adolescents. Providing education and health information about balanced nutrition is needed by adolescent girls, who are obese. Through the implementation of balanced nutrition, obesity can be prevented and overcome. The balanced nutrition animation video educational media was developed because the availability of media is still small and has not been updated according to the wishes of teenage girl and what they need. The use of appropriate educational media will affect learning outcomes. The purpose of this study is to produce an animated video about balanced nutrition in adolescent girls that is appropriate to be used as a medium for health education. The type of research used is Research and Development (RnD) with the ADDIE development model. The types of data used are primary and secondary, data collection is carried out by means of material and media testing to experts as well as small-scale trials to research subjects. The results of the media feasibility test have a value of 74% and the material feasibility of the percentage value of 91.57% while the test on research subjects gets a value of 90%. So it can be concluded that this media is appropriate to be used as an educational medium about balanced nutrition in adolescent girls. It is hoped that this animated video will become an alternative educational media for outreach activities such as the UKS program carried out by the Pandaan Health Center UPT.